Characterization and thermodynamic study of humic acid in deep groundwater at Horonobe, Hokkaido, Japan. Issue 5 (4th May 2018) - Kimuro, Shingo; Kirishima, Akira; Nagao, Seiya; Saito, Takumi; Amano, Yuki; Miyakawa, Kazuya; Akiyama, Daisuke; Sato, Nobuaki
ABSTRACT: In this study, humic substances (humic acid and fulvic acid) were isolated from deep groundwater at −350 m depth of Horonobe, Hokkaido, Japan to compare the characteristic property and reaction mechanism with generic humic acid isolated from surface soils. The size distributions of Horonobe humic substances were analyzed by size exclusion chromatography, flow-field flow fractionation, and total organic carbon measurement with ultrafiltration. All of them indicated small molecular weight and particle size of Horonobe humic acid in comparison with generic humic acids. Additionally, the simple protonation behavior of Horonobe humic substances similar to benzoic acid and/or phenol was revealed by thermodynamic quantities obtained by potentiometry and calorimetry. Consequently, molecular size and the reaction mechanism of Horonobe humic substances are different from generic humic acids, due to the characteristic origin.